The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1007/s10566-007-9048-9
|View full text |Cite
|
Sign up to set email alerts
|

Youth Worker Characteristics and Self-reported Competency as Predictors of Intent to Continue Working with Youth

Abstract: Using a web-based self-report survey, this study examined the characteristics of individuals who worked directly with youth in out-of-school time programs. Specifically, it examined the relationships among intent to continue working in the youth development field and youth program staffs' experience, training, educational background, and selfreported competency in implementing the features of positive developmental settings for youth (Eccles and Gootman, Community programs to promote youth development, 2002). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 15 publications
1
25
0
Order By: Relevance
“…In Jenkinson's (2010) project, staff reported that they felt that the improved atmosphere and sense of teamwork contributed to better quality programs. Youth workers need to feel competent in their abilities to implement quality program features that improve program quality (Hartje et al, 2008).…”
Section: Benefits To the Youthmentioning
confidence: 99%
“…In Jenkinson's (2010) project, staff reported that they felt that the improved atmosphere and sense of teamwork contributed to better quality programs. Youth workers need to feel competent in their abilities to implement quality program features that improve program quality (Hartje et al, 2008).…”
Section: Benefits To the Youthmentioning
confidence: 99%
“…A constant influx of inexperienced and inadequately trained workers diminishes the skill level, strength and effectiveness of the programs. Hartje et al (2008) find that staff retention related to working with youth is higher for staff who received job related training, view themselves as being overall competent in working with youth, have opportunities to participate in work-related decision-making, and receive help from co-workers in learning job-related skills.…”
Section: -Competency Model Design and Implementationmentioning
confidence: 90%
“…In the residential youth care environment, research has revealed that positive developmental outcomes for youth are linked with residential programs that are effective in providing physical and psychological safety, appropriate structure, supportive relationships, opportunities to belong, opportunities for skill building, and integration of family, school, and community efforts (Eccles and Grootman, 2002). For a program to be effective in these dimensions, youth care workers need to be aware of these benefits, and feel competent in their ability to implement these features (Hartje et al, 2008). Studies have consistently identified caregiver specialized training and education as one of the strongest predictors of child care quality (Gable and Halliburton, 2003).…”
Section: -Competency Model Design and Implementationmentioning
confidence: 99%
See 2 more Smart Citations